Themes Innovation for Making Educational Game Module to Prevent Stunting at Family Level for Toddler in Surabaya: A Qualitative Study - Annas Buanasita; Taufiqurrahman; Heni Hendriyani; Inne Soesanti (Politeknik Kesehatan Kemenkes Surabaya, 2026)
Introduction: Approximately 66.6% of programs providing information, education and communication have been carried out to prevent stunting, but need to improve according to the need of target audience. After the covid-19 pandemic, there are challenges for outreach the IEC activities with an approach that directly reaches the family level. Aims: This study aims to find methods and themes of the IEC module that are more desirable by the community in preventing stunting. Methods: Qualitative research method with FGD (Focus Group Discussion) in 2 urban village locations in the city of Surabaya, followed by In-depth Interviews on several key informants. The descriptive analysis was divided into three stages, namely reduction, data presentation, and thematic conclusion drawing. Results: Based on the results of the FGD, 3 desired module topics were obtained, namely (1) early detection of stunting independently at the family level (2) the dangers of stunting for the growth and development of children's intelligence and (3) good eating behavior to prevent stunting. The method chosen is an interactive emo demo method with games while learning. Study showed that the emo demo approach was better at the family level considering that many mothers with stunting children often did not come to the posyandu. Conclusion: The early detection, the cognitive dangers and the diet in preventing stunting were three themes chosen by community with emo demo method to deliver in the family level.The strength of this approach is to invite mothers to learn through playing and raising awareness in preventing stunting.